Investigation of the Material Point Method in the simulation of Cone Penetration Tests in dry sand. (February 2021) - Martinelli, Mario; Galavi, Vahid
Abstract: Cone penetration tests (CPTs) are widely used in geotechnical engineering for soil characterization and parameter determination. Throughout the years, experimental data have been used to determine correlations between CPT data and soil properties, such as stiffness or strength. Recent progress in advance numerical methods allows the simulation of the full CPT penetration by overcoming the limitations related to extreme deformations. The use of these numerical techniques provides new prospective to the soil characterization and determination of soil parameters, especially for the settings where limited (or no) experimental data is available and existing correlations are not accurate, or absent. This paper presents a numerical framework based on the Material Point Method (MPM) to simulate CPT in dry sand. First, it is proven that the calculation scheme is stable and accurate. Then, the model results are validated against chamber test data in terms of both cone resistance and displacement field during the penetration. Finally, some considerations about the formulation of the constitutive models of soils are presented, specifically oriented for CPT applications.